Pengaruh Pelatihan Kerja, Kepuasan Kerja dan Kompensasi Terhadap Kinerja Karyawan Barberia (PT.Adi Reka Mampras Sam Purna) Wilayah DKI Jakarta - Andriyani, Riska; Tarmizi, Achmad (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to determine and analyze the influence of job training, job satisfaction and compensation on employee performance. This type of research is associative research. The instrument of this research is a questionnaire with a Likert scale. The population in this study was all 52 employees. Saturated sampling technique. The number of samples required in this research is 52 people. Data collection techniques in this research are literature study, observation, questionnaires and interviews. The testing technique used is multiple linear regression with results Y = 2.487+ 0.448 (X1) + 0.233 (X2) + 0.297 (X3) and hypothesis testing consisting of the t test and f test. The results of this research are: (1) There is a positive and insignificant influence between job training on employee performance as indicated by the calculated t value of 2.226 > 2.009 (2) There is a positive and insignificant influence between job satisfaction and employee performance as indicated by the calculated t value 0.982 < 2.009 (3) There is a positive and insignificant influence between employee performance compensation as indicated by the calculated t value 1.434 < 2.009 (4) There is a positive and significant influence between Job Training, Job Satisfaction and Compensation on Employee Performance as indicated by the calculated f value 5.840 > 2.79 correlation coefficient (R) of 0.741, which means the relationship between variables is quite strong and the coefficient of determination is 0.549, which means 54.9% of the three independent variables influence employee performance simultaneously and the remainder is influenced by other variables, amounting to 45.1%.This research aims to determine and analyze the influence of job training, job satisfaction and compensation on employee performance. This type of research is associative research. The instrument of this research is a questionnaire with a Likert scale. The population in this study was all 52 employees. Saturated sampling technique. The number of samples required in this research is 52 people. Data collection techniques in this research are literature study, observation, questionnaires and interviews. The testing technique used is multiple linear regression with results Y = 2.487+ 0.448 (X1) + 0.233 (X2) + 0.297 (X3) and hypothesis testing consisting of the t test and f test. The results of this research are: (1) There is a positive and insignificant influence between job training on employee performance as indicated by the calculated t value of 2.226 > 2.009 (2) There is a positive and insignificant influence between job satisfaction and employee performance as indicated by the calculated t value 0.982 < 2.009 (3) There is a positive and insignificant influence between employee performance compensation as indicated by the calculated t value 1.434 < 2.009 (4) There is a positive and significant influence between Job Training, Job Satisfaction and Compensation on Employee Performance as indicated by the calculated f value 5.840 > 2.79 correlation coefficient (R) of 0.741, which means the relationship between variables is quite strong and the coefficient of determination is 0.549, which means 54.9% of the three independent variables influence employee performance simultaneously and the remainder is influenced by other variables, amounting to 45.1%.